2020
DOI: 10.1242/dev.184663
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that ABC transporter-mediated autocrine export of an eicosanoid signaling molecule enhances germ cell chemotaxis in the colonial tunicate Botryllus schlosseri

Abstract: The colonial ascidian Botryllus schlosseri regenerates the germline during repeated cycles of asexual reproduction. Germline stem cells (GSCs) circulate in the blood and migrate to new germline niches as they develop and this homing process is directed by a Sphigosine-1-Phosphate (S1P) gradient. Here, we find that inhibition of ABC transporter activity reduces migration of GSCs towards low concentrations of S1P in vitro. In addition, inhibiting phospholipase A2 (PLA2) or lipoxygenase (Lox) blocks chemotaxis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The amount of IA6 cells is not noticeably different between the two species (Additional file 9 : Fig. S4) [ 24 , 36 ]; thus, either the cell populations are different, and B. diegensis retains a mobile pluripotent somatic progenitor, or there is not an appropriate signal or niche for germline precursors to transdifferentiate in B. schlosseri .…”
Section: Discussionmentioning
confidence: 99%
“…The amount of IA6 cells is not noticeably different between the two species (Additional file 9 : Fig. S4) [ 24 , 36 ]; thus, either the cell populations are different, and B. diegensis retains a mobile pluripotent somatic progenitor, or there is not an appropriate signal or niche for germline precursors to transdifferentiate in B. schlosseri .…”
Section: Discussionmentioning
confidence: 99%
“…Two broad and potentially interrelated hypothesises could explain the basis of germline parasitism: first, the winner GSCs could be faster at detecting, migrating to and occupying the developing germline niche; and/or there may be competition for maintaining access to the niche during gametogenesis. Using a combination of in vitro transwell migration assays and in vivo analyses, we had previously found that the migration of GSCs is controlled by a gradient of sphingosine-1-phosphate (S1P) secreted by the newly developing niche [20,21], and also…”
Section: Winner Gscs Have Increased Migration Capabilities Compared T...mentioning
confidence: 99%
“…that S1P chemotaxis may also be dependent on the generation of an autonomous gradient of the bioactive lipid, 12-S-HETE [21]. In order to characterize general migration mechanisms, these studies were done using multiple wild-type genotypes, without regard to the competitive phenotype of the individuals.…”
Section: Plos Onementioning
confidence: 99%
“…Colonial ascidians belonging to the genus Botrylloides are known for their whole-body regeneration (WBR) phenomenon, in which the entire colony regenerates from only a small portion of the vasculature [153][154][155]. Recently, Kassmer and collaborators [154] identified a population of bloodborne candidate SCs responsible for WBR in the species Botryllus schlosseri. These integrinalpha-6-positive (Ia6+) cells, which constantly divide in healthy colonies, also express genes associated with pluripotency.…”
Section: Tunicatesmentioning
confidence: 99%